Roasting of Carbonaceous Auriferous Pyrite and Arsenopyrite Flotation Concentrate (Journal of Science and Technology, 2016)
The roasting conditions for gold ore flotation concentrate from two sources have been studied. Temperatures from 450 to 850°C were employed for one-stage roasting in air for 6 hours. Two-stage roasting was also carried out employing 550°C followed by 750°C for a total time of 2, 4, and 6 hours. The surface areas of the calcines were measured using the B.E.T. nitrogen adsorption technique; the calcine were then leached for gold in 0.1% NaCN solution over a 24 hour period. Results showed that for the one-stage process gold extraction was maximum at 650-700°C for both sample A and B respectively. The surface area was found to decrease with increasing roasting temperature and this was believed to be the cause of the low gold extraction obtained above 700°C. At the lower temperatures below 650°C the low extraction was ascribed to the presence of uneliminated C, S. and As. Two-stage roasting of sample B for 6 hours yielded calcines with higher surface area and consequently a higher gold extraction.